Implications and Investigations of Pharmacy Benefit in the United States - Watanabe, Jonathan Hirohiko (My University, 2013)
Medicaid clients are among the most at-risk members for poor health outcomes in society and this safety net health care is critical for assuring continuous access to medical care. We will describe the importance of curtailing unnecessary drug spend as well as generic utilization mechanisms already applied by payers. We will describe the background, implementation, and early findings of a prescriber feedback report card program to improve generic utilization in the Washington State Medicaid system. We quantified the association between possession of prescription drug coverage and likelihood of experiencing an emergency room [ER] visit and hospitalization in the adult United States population with private health insurance. For the outcomes of ER visits and hospitalizations, the ORs were 1.05 (95% confidence interval [CI], 0.95 to 1.15) and 1.07 (95% CI, 0.95-1.22) respectively using propensity score matching. Indicating a non-significant increase in odds of the outcomes of ER visit and hospitalization for patients possessing drug coverage . Multiple logistic regression produced similar findings. For the outcomes of ER visit and hospitalization, the adjusted ORs were 1.03 (0.96-1.12) and 1.01 (0.91-1.21) respectively. Prescription drug coverage in the United States was not associated with a reduction in likelihood of ER visit or hospitalization in this assessment pooling ten years of cross-sectional data. To estimate the reduction in adherence and medication supplied for patients that experience increases in average monthly copay over time for three therapeutically distinct drugs for chronic syndrome management using a nationally representative Commercial Claims databaseIncrease in $5 or more or $10 or more for average monthly copay was associated with a statistically significant reduction in MPR for all three drugs. Measured by generalized estimating equations, change in MPR varied from a minimum loss of 0.024 for simvastatin with a $5 or more increase in copay to a maximum loss of 0.063 for insulin glargine with $10 or more increase. This equates to a minimum loss of days supply 8.8 to 23.0 for simvastatin and insulin glargine respectively. Copay increases are associated with significant reductions in adherence of chronic medications necessary for optimal disease control.
Thesis (Ph.D.)--University of Washington, 2012
Keywords: Adherence; Insurance; Medical Care; Outcomes; Pharmacy; Statistics; Pharmaceutical sciences; Health sciences; Economics; to be assigned